2017
DOI: 10.1055/s-0036-1589069
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine-Based Activation of Triphenylphosphine for the Functionalization of Alcohols

Abstract: The use of hypervalent iodine reagents as a general tool for the activation of PPh3 and its application to the functionalization of alcohols is reported. Combination of PPh3 with PhICl2 or TolIF2 gives dihalophosphoranes that are characterized by 31P NMR, however, with PhIOAc2, PhI(OTFA)2, or the cyclic chloro(benzoyloxy)iodane, no phosphoranes were observed. Reaction of these iodanes with PPh3 in the presence of primary, secondary, or tertiary alcohols results in either halogenation or acyl-transfer products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In fact, difluorotriphenylphosphorane has been successfully applied as deoxyfluorination reagent to convert primary and secondary alcohols into fluoroalkanes at reaction temperatures above 140 °C. 42 As a proof of principle, the deoxyfluorination of 1-hexanol was performed with the TPP-Fluor reagent and gave 1-fluorohexane in 22% yield. We also used TPP-Fluor for the preparation of acyl fluorides directly from carboxylic acids.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, difluorotriphenylphosphorane has been successfully applied as deoxyfluorination reagent to convert primary and secondary alcohols into fluoroalkanes at reaction temperatures above 140 °C. 42 As a proof of principle, the deoxyfluorination of 1-hexanol was performed with the TPP-Fluor reagent and gave 1-fluorohexane in 22% yield. We also used TPP-Fluor for the preparation of acyl fluorides directly from carboxylic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation of primary and secondary alcohols was observed with triphenylphosphine and 1, giving products 192 and 194 in 56 % and 47 % yield, respectively (Scheme 33, a and b). [64] Trifluoroacetylation of primary, secondary and tertiary alcohols was similarly achieved with (bistrifluoroacetoxyiodo)benzene, giving trifluoroacetates 193, 195 and 196 in up to 84 % yield. Chlorinated benziodoxolone 8 was also tested, and afforded chlorination products (e.g., 197, 198) with primary and secondary alcohols and predominantly benzoylation products (e.g., 199) with tertiary alcohols (Scheme 33 d).…”
Section: 5b Esterification and Amidation Reactionsmentioning
confidence: 99%
“…Murphy and co-workers demonstrated that the reaction of triphenylphosphine with PhICl 2 (218) [67] or TolIF 2 (25) [64] readily produced dihalotriphenylphosphoranes Ph 3 PCl 2 (219) and Ph 3 PF 2 (220). When phosphorane 219 was generated in the presence of carboxylic acids, the corresponding acyl chlorides were readily produced, which could in turn be trapped with amine, alcohol and diazomethane nucleophiles.…”
Section: 5d Halogenation Reactionsmentioning
confidence: 99%